Sanitasi Lingkungan Rumah Tangga yang Berwawasan Lingkungan - Muhammad Ardi; Faizal Amir; Bakhrani A. Rauf (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. The objectives of this PKM are as follows: (1) increase partners 'knowledge of environmental sanitation, particularly drainage and storage tanks for dirty water and rainwater, and (2) improve partners' skills in making drainage and storage tanks for dirty water and rainwater. The methods used are: (1) Performing licensing, site preparation, and socialization. The strategy used is discussion and question and answer. (2) Conducting counseling. The strategies used are lectures, discussions, and questions and answers. (3) Conduct training and mentoring. The strategies used were demonstration, discussion, and question and answer. The results achieved were: (1) partners had knowledge of environmental sanitation, especially drainage and storage tanks for dirty water and healthy rainwater, (2) partners had skills in making environmental sanitation constructions , particularly drainage and storage tanks for dirty water and healthy rainwater, and (3) a unit for collecting dirty water and rainwater has been created to function properly as an alternative to improve the quality of the environment in Kanaungan Village.